Acacia catechu Willd. Extract Protects Neuronal Cells from Oxidative Stress-Induced Damage - Elda Chiaino; Roberto Stella; Caterina Peggion; Matteo Micucci; Roberta Budriesi; Laura Beatrice Mattioli; Carla Marzetti; Federica Pessina; Massimo Valoti; Maria Frosini (MDPI AG, 2021)
Oxidative stress (OS) and the resulting reactive oxygen species (ROS) generation and inflammation play a pivotal role in the neuronal loss occurring during the onset of neurodegenerative diseases. Therefore, promising future drugs that would prevent or slow down the progression of neurodegeneration should possess potent radical-scavenging activity. Acacia catechu Willd. heartwood extract (AC), already characterized for its high catechin content, is endowed with antioxidant properties. The aim of the present study was to assess AC neuroprotection in both human neuroblastoma SH-SY5Y cells and rat brain slices treated with hydrogen peroxide. In SH-SY5Y cells, AC prevented a decrease in viability, as well as an increase in sub-diploid-, DAPI positive cells, reduced ROS formation, and recovered the mitochondrial potential and caspase-3 activation. AC related neuroprotective effects also occurred in rat brain slices as a reversal prevention in the expression of the main proteins involved in apoptosis and signalling pathways related to calcium homeostasis following OS-mediated injury. Additionally, unbiased quantitative mass spectrometry allowed for assessing that AC partially prevented the hydrogen peroxide-induced altered proteome, including proteins belonging to the synaptic vesicle fusion apparatus. In conclusion, the present results suggest the possibility of AC as a nutraceutical useful in preventing neurodegenerative diseases.